Citizen Centric Approach for Skill Testing and Certification of CTEVT - Maharjan, Mahesh; Maharjan, Suresh (MVIC Journal of Management and Information Technology, 2025)
This study is on citizen centric approach for skill testing and certification of CTEVT, Nepal. The researchers explore current tools and technologies that have been adopted by CTEVT and explore e-Governance approaches for skill testing and certification of CTEVT, Nepal. Finally, they tried to automate the skill testing and certification of CTEVT, Nepal. Various research literatures were studied and data collected from 110 respondents using 26 interrelated survey questions to explore the citizen centric approach for skill testing and certification. This study adopted quantitative research design and followed random sampling. Traditional craft persons, occupational groups, informally and/or formally trained people and workforce of industry enroll to CTEVT for recognition of their skills through skill testing and certification. They have to wait in long time in an administrative process and pay high cost to avail services from CTEVT due to frequent travel. On the other hand, business organization are not getting certified workers and also facing problems in verifying certified workers from CTEVT. The service seekers are not getting the skill testing and certification services in convenient, equitable, transparent and economical manner around the clock. Based on the result of data analysis, the researcher has proposed an automated e-service delivery system framework for skill testing and certification so that CTEVT can provide quality of service and value to user service in terms of improved service, reduced cost and time saving to service seekers.